Membongkar Wacana Sertifikasi Dai Menangkal Radikalisme dalam Program Televisi - Abd Munib (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This scientific work was written to reveal the discourse on dai certification that has been being discussed since 2017. Many media, both print and broadcast-based, have highlighted this discourse. The broadcast media also discussed the discourse so it was natural because the public's consideration saw certification as something important in the midst of the rise of preachers on the pulpit armed with doubtful and doubtful knowledge and conveying religious messages intolerantly and then understanding radicalism. The object of this research is the Prime Talk program which aired on Metro Tv on 19 November 2019 with the title Dai Certification, Counteracting Radicalization using qualitative methods with critical discourse analysis by Van Dijk's model. The author's important notes from the diaphragm presented in this program also serve as data in revealing the discourse Based on the analysis of Van Dijk's model of critical discourse, it shows that the 19 Nomvember 2019 edition of Prime Talk entitled Dai Certification, Warding Radicalization builds five discourses: (1) recently religious messages are often conveyed by speakers whose religious knowledge is shallow so they tend to be extreme; (2) standardization of dai to print frendly dai against the Republic of Indonesia; (3) important dai certification applied throughout Indonesia; (4) Indonesia has been slow in certifying dai; and (5) the security apparatus must be responsive to reduce intolerant conditions.